Counseling About Anemia In Pregnant Women And Adolescent Girls In Rt 2 Batu Urip Village, Lubuk Linggau City - Bayanti, Anggi Nur; Resmi , Ermi; Ernani , Ernani; Sari , Ferlisa Junia; Oktaviana , Nafsia; Murwati , Murwati (Jurnal Pengabdian Mandiri, 2025)
Anemia is a nutritional problem in the world. Based on the World Health Organization/WHO report, more than 30% or 2 billion people in the world have anemia. The prevalence of anemia in Indonesia, which is 21,7% with anemia sufferers aged 5-14 years is 26.4% and 57% aged 15-24 years. The data shows that anemia is a nutritional problem that is often experienced by teenagers. According to Riskesdas data, the prevalence of iron deficiency anemia is found in adolescent girls at 22.7%, while iron deficiency anemia in adolescent boys is 12.4%. Anemia that is most often found in pregnancy is anemia due to iron deficiency caused by lack of iron intake in food, absorption disorders, increased iron requirements. Every year around 40% of pregnant women around the world experience anemia mainly due to iron deficiency. At the end of the extension process, pregnant women and young women in RT 2 Batu Urip Village can understand and understand about Anemia.The method used in counseling about anemia is lectures and questions and answers as well as distributing leaflets.The results of counseling activities about Anemia in Pregnant Women and Young Women in RT 2 Batu Urip Village are the average pretest knowledge of pregnant women and young women about Anemia beforebeing given counseling about Anemia is <50 in the category less. Then the average post-test knowledge of pregnant women and teenage girls after being given counseling about Anemia is >50 in the good category.